The Implementation of Ibn al-Haytham’s Method for Determining Qibla Direction Using Raspberry Pi - Sanjaya, W. S. Mada; Roziqin, Akhmad; Anggraeni, Dyah; Mamat, Mustafa (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2022)
Ibn al-Haytham or better known as Alhazen (965-1040 AD) was a great Muslim scientist who mastered many disciplines. One of his works entitled "Qawl fi Samt al-Qibla bi al-Hisab" describes a mathematical method for determining the direction of Qibla. In this paper, Ibn al-Haytham's algorithm is modified, thus the algorithm can determine the Qibla direction on the entire surface of the globe. Then, Ibn al-Haytham's mathematical method is compared with modern spherical trigonometry methods and our previous research using al-Biruni’s method. The computational results show that all methods have the same accuracy, and show that ibn al-Haytham's method is still relevant now. Therefore, the modified ibn al-Haytham method algorithm was implemented to develop a Qibla direction device and interface based on Raspberry Pi 4, GPS module, digital compass, and Processing 3 software. The implementation results show that the device can display the Qibla direction interface according to numerical calculations with high accuracy, real-time, and dynamic interface.